QTLs Regulating the Contents of Antioxidants, Phenolics, and Flavonoids in Soybean Seeds Share a Common Genomic Region - Li, Man-Wah; Muñoz, Nacira B.; Wong, Chi-Fai; Wong, Fuk-Ling; Wong, Kwong-Sen; Wong, Johanna Wing-Hang; Qi, Xinpeng; Li, Kwan-Pok; Ng, Ming-Sin; Lam, Hon-Ming (Frontiers in Plant Science, 2016)
Soybean seeds are a rich source of phenolic compounds, especially isoflavonoids, which are important nutraceuticals. Our study using 14 wild and 16 cultivated soybean accessions shows that seeds from cultivated soybeans generally contain lower total antioxidants compared to their wild counterparts, likely an unintended consequence of domestication or human selection. Using a recombinant inbred population resulting from a wild and a cultivated soybean parent and a bin map approach, we have identified an overlapping genomic region containing major quantitative trait loci (QTLs) that regulate the seed contents of total antioxidants, phenolics, and flavonoids. The QTL for seed antioxidant content contains 14 annotated genes based on the Williams 82 reference genome (Gmax1.01). None of these genes encodes functions that are related to the phenylpropanoid pathway of soybean. However, we found three putative Multidrug And Toxic Compound Extrusion (MATE) transporter genes within this QTL and one adjacent to it (GmMATE1-4). Moreover, we have identified non-synonymous changes between GmMATE1 and GmMATE2, and that GmMATE3 encodes an antisense transcript that expresses in pods. Whether the polymorphisms in GmMATE proteins are major determinants of the antioxidant contents, or whether the antisense transcripts of GmMATE3 play important regulatory roles, awaits further functional investigations.